An open-label study assessing the safety and efficacy of alitretinoin in patients with severe chronic hand eczema unresponsive to topical corticosteroids - Dirschka, Thomas; Reich, K.; Bissonnette, R.; Maares, J.; Brown, T.; Diepgen, Thomas L. (Clinical and experimental dermatology, 2011)
Background. Blinded, controlled studies have found that oral alitretinoin is well tolerated and effective in the treatment of severe chronic hand eczema (CHE). Aim. To assess the safety and efficacy of oral alitretinoin in patients with severe CHE in an open-label study using flexible dosing and a new measurement of patient-relevant benefits. Methods. In total, 249 patients aged 18-75 years with severe CHE unresponsive to treatment with topical corticosteroids received alitretinoin 30 mg once daily for up to 24 weeks. Safety assessments included adverse events (AEs) and laboratory tests. Efficacy assessments included Physician’s Global Assessment (PGA), the Modified Total Lesion Symptom Score, Patient’s Global Assessment and extent of disease, as well as intensity of pain and pruritus as determined by visual analogue scale (VAS) and a categorical scale for pruritus. Results. Alitretinoin was well tolerated when given for up to 24 weeks. Dose reduction occurred in 16.5% of patients. Dose interruption was required for 15.7% of patients, most commonly for headache. AEs and laboratory changes comprised effects typical of the retinoid class. A PGA response of ‘clear’ or ‘almost clear’ hands was reported for 46.6% of patients, similar to the response rate seen in blinded trials. Results of VAS and categorical assessments of pruritus provided supporting evidence of efficacy, and treatment was assessed as providing meaningful benefits to patients. Conclusions. Oral alitretinoin 30 mg was well tolerated and effective, and provided distinct therapeutic benefits in severe CHE, as assessed by patients.
First published: 10 November 2010
Gesehen am 13.06.2022